FINANCIAL RISK MANAGEMENT AND PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Adesina Olufemi Dadepo Ph. D, FCIB, ACA; Ochei Ngozi Fidelia; Adesina Tolulope Oluwatoyin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study investigates the impact of financial risks, specifically credit risk, operational risk, and market risk on the profitability of listed Deposit Money Banks (DMBs) in Nigeria over the period 2014–2023. Using fixed-effects panel regression on data from 10 listed DMBs, the study examines the effects of three risk-weighted ratios: credit risk, operation risk and market risk (CRTWR, ORTWR, MRTWR) and a risk-adjusted spread ratio (RISASR) on Earnings Per Share (EPS), Return on Assets (ROA), and Return on Equity (ROE), while controlling for bank size (BSIZE). Results reveal that credit risk (CRTWR) exerts a significant positive effect on all profitability metrics, suggesting that Basel III-compliant capital allocation enhances financial performance. Operational risk (ORTWR) consistently reduces profitability across all measures, reflecting the adverse impact of fraud and IT failures in Nigeria's digitally evolving banking sector. Market risk (MRTWR) shows only marginal significance for EPS, with no significant effect on ROA or ROE, indicative of effective hedging practices. RISASR is insignificant across all models. Bank size (BSIZE) positively moderates profitability, confirming economies of scale advantages. The findings have important implications for bank managers, regulators, and the Central Bank of Nigeria (CBN) in designing risk-sensitive capital and operational frameworks.